Comparison of mainstream (Capnostat 5) and two low-flow sidestream capnometers (VM-2500-S and Capnostream) in spontaneously breathing rabbits anesthetized with a Bain coaxial breathing system. (July 2020) - Duke-Novakovski, Tanya; Fujiyama, Masako; Beazley, Shannon G.
Abstract: Objective: To evaluate agreement with PaCO2 of two low sampling rate sidestream capnometers and a mainstream capnometer in rabbits and the effect of using high fresh gas flow from a Bain coaxial breathing system. Study design: Prospective, crossover study. Animals: A total of 10 New Zealand White rabbits weighing 3.4 ± 0.3 kg [mean ± standard deviation (SD)]. Methods: Two sidestream analyzers (Viamed VM-2500-S and Capnostream 35) with a sampling rate of 50 mL minute –1 and a mainstream capnometer (Capnostat 5) were tested. All capnometers used infrared spectroscopy and advanced microprocessor technology. Rabbits were anesthetized and intubated with noncuffed endotracheal tubes of 3 mm internal diameter and adequate seal. A sidestream sampling adapter or the mainstream capnometer was attached to the endotracheal tube and connected to a Bain coaxial breathing system. Oxygen (1.5 L minute –1 ) delivered sevoflurane to maintain anesthesia. An auricular artery catheter allowed blood sampling for PaCO2 analysis corrected to rectal temperature. Inspired and end-tidal carbon dioxide (Pe′ CO2 ) measurements were recorded during blood sample withdrawal. From each rabbit, 10 paired PaCO2 /Pe′ CO2 measurements were obtained. Each rabbit was recovered from anesthesia and was anesthetized again with an alternate capnometer after 1 week. Data were analyzed using Bland–Altman and two-way anova for repeated measures. Results: Analysis included 100 paired samples. Negative bias reflects underestimation of PaCO2 . Bland–Altman mean (±1.95 SD) was –16.7 (–35.2 to 1.8) mmHg for Capnostat 5, –27.9 (–48.6 to –7.2) mmHg for Viamed, and –18.1 (–34.3 to –1.9) mmHg for Capnostream. Viamed PaCO2 –Pe′ CO2 gradient was greater than other two capnometers. Conclusions: All three capnometers underestimated PaCO2 . Capnostat 5 and Capnostream performed similarly. Clinical relevance: These capnometers underestimated PaCO2 in spontaneously breathing rabbits anesthetized using a Bain coaxial breathing system with high fresh gas flows.